The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/microorganisms9020398
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Colistin Resistance Gene mcr-1 Detected on an IncI2 Plasmid in Salmonella Typhimurium Sequence Type 19 from a Healthy Pig in South Korea

Abstract: Colistin is considered the last resort for the treatment of multi-drug resistant Gram-negative bacterial infections. We studied colistin resistance and the mcr-1 gene carriage in Salmonella isolates recovered from food animals in South Korea between 2010 and 2018. Colistin resistance was found in 277 isolates, predominantly in Salmonella Enteritidis (57.1%) and Salmonella Gallinarum (41.9%). However, the mcr-1 gene was identified in only one colistin-resistant Salmonella Typhimurium (MIC = 16 µg/mL) isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…In these ceftriaxone-resistant Salmonella isolates, we found two mcr -1-positive isolates; interestingly, one of them was colistin susceptible, with a truncated mcr -1 allele. mcr -1-positive Salmonella isolates have been previously reported in Brazil ( Rau et al, 2020 ), Spain ( Trujillo-Soto et al, 2019 ), South Korea ( Moon et al, 2021 ), and China ( Lu et al, 2019 ), and the mcr -1 gene was found to be normally located on IncI2, IncHI2, and IncX4 plasmid types, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In these ceftriaxone-resistant Salmonella isolates, we found two mcr -1-positive isolates; interestingly, one of them was colistin susceptible, with a truncated mcr -1 allele. mcr -1-positive Salmonella isolates have been previously reported in Brazil ( Rau et al, 2020 ), Spain ( Trujillo-Soto et al, 2019 ), South Korea ( Moon et al, 2021 ), and China ( Lu et al, 2019 ), and the mcr -1 gene was found to be normally located on IncI2, IncHI2, and IncX4 plasmid types, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Comparisons with previously published Salmonella and E.coli IncI2 plasmids (Table S1), carrying mcr-1.1 gene, are shown in Figure 2. IncI2 plasmid pS7627-2 has a similar plasmid backbone and a similar genetic environment surrounding the mcr-1.1 gene (nikB-mcr-1.1-PAP) compared to other IncI2 plasmids (pCESA664-3, pCESA244-2, pK18JST013) previously isolated in China and Korea [31]. The ISApl1 insertion sequence belonging to IS30 family was not identified near mcr-1.1.…”
Section: Salmonella Bovismorbificans Slr1_7627mentioning
confidence: 94%
“…A PCR assay was performed to detect the most frequently reported carbapenem resistance genes in South Korea (bla IMP , bla VIM , bla OXA-48 -like, bla NDM , and bla KPC ) (Table S2) [29,30]. Whole-genome sequencing was performed using PacBio RS II (Pacific Biosciences, Menlo Park, CA, USA), as previously described [31]. Antimicrobial resistance genes were analyzed by the Center for Genomic Epidemiology (http://www.genomicepidemiology.org/; accessed on 18 February 2021).…”
Section: Polymerase Chain Reaction (Pcr) and Whole-genome Sequencingmentioning
confidence: 99%